2021
DOI: 10.1155/2021/9523039
|View full text |Cite
|
Sign up to set email alerts
|

Single and Combined Neuroimaging Techniques for Alzheimer’s Disease Detection

Abstract: Alzheimer’s disease (AD) consists of the gradual process of decreasing volume and quality of neuron connection in the brain, which consists of gradual synaptic integrity and loss of cognitive functions. In recent years, there has been significant attention in AD classification and early detection with machine learning algorithms. There are different neuroimaging techniques for capturing data and using it for the classification task. Input data as images will help machine learning models to detect different bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 114 publications
(99 reference statements)
0
10
0
Order By: Relevance
“…Lifelong exposures to PM 2.5 above the current USEPA standard are associated with a significant decrease in gray matter from higher order cortical regions, commonly associated with Alzheimer's, Parkinson's and FTD in 42.7 ± 9.3 years old, healthy, college educated, Metropolitan Mexico City residents [45][46][47][48][49][50][51][52][53][54][55][56]. Significant caudate nuclei and cerebellar gray and white matter atrophy were also documented [57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 96%
“…Lifelong exposures to PM 2.5 above the current USEPA standard are associated with a significant decrease in gray matter from higher order cortical regions, commonly associated with Alzheimer's, Parkinson's and FTD in 42.7 ± 9.3 years old, healthy, college educated, Metropolitan Mexico City residents [45][46][47][48][49][50][51][52][53][54][55][56]. Significant caudate nuclei and cerebellar gray and white matter atrophy were also documented [57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Discussionmentioning
confidence: 96%
“…The diagnosis of brain disorders including PD, AD, and schizophrenia (SZ) is often greatly aided by multimodality neuroimaging data [ 184 ]. Various clinical investigations have described the reliable detection of PD using a combination of neuroimaging modalities, such as EEG-fMRI [ 185 , 186 , 187 , 188 ], MRI-PET [ 189 , 190 , 191 , 192 ], fMRI-MEG [ 193 , 194 ], and fMRI-sMRI [ 195 , 196 , 197 ]. Diagnosis of PD using multimodality neuroimaging data is complicated and time-consuming for doctors, despite all the advantages.…”
Section: Discussion: Challenges and Recommendationsmentioning
confidence: 99%
“…Studies based on ML and CNN using multimodal have shown their ability and effectiveness in alleviating the limitations of unimodal data use and thus improving the prediction models' accuracy in the diagnosis of the disease. 20,21 Most studies concentrated on combining DTImaps and sMRI in the screening of AD. For example, Marzban et al 22 used DTI-derived measurements (FA, MD, and mode of diffusivity [MO]), and GM segmented from T1-weighted sMRI.…”
Section: Related Workmentioning
confidence: 99%